Ring-expansion reaction for the synthesis of 2-(trifluoromethyl)oxazoles and 3-(trifluoromethyl)-1, 2, 4-triazines. (28th September 2022) - Teng, Yun; Fang, Tingyu; Lin, Zitong; Qin, Lu; Jiang, Mengfan; Wu, Wei; You, Yi; Weng, Zhiqiang
Graphical abstract: The synthesis of 2-(trifluoromethyl)oxazoles through ring-expansion reaction of 2 H -azirine with trifluoroacetic anhydride is reported. The 2-(trifluoromethyl)oxazole compounds can be easily converted into 3-(trifluoromethyl)-1, 2, 4-triazines through hydrazinolysis reaction. Highlights: A method for synthesis of 2-(trifluoromethyl)oxazoles and 3-(trifluoromethyl)-1, 2, 4-triazines was developed. Various trifluoromethyl oxazoles and triazines were synthesized in moderate to excellent yields. A variety of functional groups were tolerated. Abstract: A ring-expansion reaction of 2 H -azirine with trifluoroacetic anhydride for the synthesis of 2-(trifluoromethyl)oxazoles is disclosed. The reaction features readily available reactants, relatively mild conditions, and high yields of products. The generated 2-(trifluoromethyl)oxazole core could be easily converted into 3-(trifluoromethyl)-1, 2, 4-triazines through hydrazinolysis reaction.